Tobacco consumption and associated factors among tribal adolescent students in Terai-Dooars region, West Bengal - Tirkey, Louis; Lakra, Rupanjli (Indian Journal of Community Health, 2024)
Background: Tobacco is one of the major causes of preventable deaths worldwide. Around the world, tobacco is one of the leading causes of tobacco-related cancer. Objectives: To estimate the proportion of tobacco use among tribal adolescents in Terai-Doars region, and to determine the related risk factors. Methodology: A school based cross-sectional study was conducted among 680 tribal adolescent students of government schools in Teria-Dooars region of West Bengal, from April 2022 to October 2022. After obtaining consent, data on socio-demographics and tobacco consumption were collected. Significance was tested using multivariable logistic regression. Results: The proportion of tobacco consumption among tribal adolescent students was found to be 45.7%. Male (58.1%) and female (28.2%) adolescents were found to be regular consumers. Male adolescents primarily prefer smokeless tobacco, with 58% starting their habit between 12-15 years age. Male adolescents preferred smokeless tobacco, with a significant proportion starting their habit between 12-15 years (58%). High consumption of Khaini (52.6%), Guthka (46.6%), and Cigarette (42.4%) is observed. Age (<0.001), sex (<0.001), religion (0.029), socio-economic level (0.004), and family history (0.003) significantly associated with tobacco consumption. Conclusions: Overall proportion of tobacco use was high among the tribal adolescents, with most starting smoking at an early age. The major risk factor that contributed was the family members' tobacco use.